Inferiority feelings mediate the impact of subjective social support on anxiety/depression symptoms in individuals with physical disabilities - Liu, Yiyang; Xu, Wenjing; Liu, Shanshan; Song, Yuqing; Li, Lin; Li, Shunfei; Chen, Hongguang (Frontiers in Public Health, 2024)
BackgroundPersons with physical disabilities are more likely to suffer from psychological symptoms and inferiority feelings, and social support plays an important role in improving those symptoms. However, the interaction between psychological symptoms, inferiority feelings and social support is yet to be understood.MethodsA cross-sectional study was conducted to investigate anxiety, depression, and inferiority feelings among individuals with physical disabilities in a Chinese sample. The questionnaire included the Generalized Anxiety Disorder 7, Patient Health Questionnaire 9, Self-designed Disability Questionnaire, and Social Support Rating Scale including three dimensions: subjective social support, objective social support and utilization of social support.ResultsOut of the 1,453 respondents with physical disabilities, 49.7, 60.4, and 62.5% reported experiencing anxiety, depression, and inferiority feelings, respectively. Factors such as time since identification of physical disabilities, comorbidities, daily travel, social interaction, internet use, subjective social support, and inferiority feelings were found to be associated with anxiety or depression symptoms among physically disabled individuals. Subjective social support was found to be associated with inferiority feelings, which partly mediated the effect of subjective social support on anxiety symptoms by 37.4% and depression symptoms by 28.7%.ConclusionThis study highlights the importance of addressing the psychological well-being of physically disabled individuals in addition to their physical rehabilitation. Psychological intervention strategies should focus on improving subjective social support and reducing inferiority feelings, particularly among vulnerable groups.